Kininase 1 As a Preclinical Therapeutic Target for Kinin B1 Receptor in Insulin Resistance - Haddad, Youssef; Couture, Réjean (Frontiers in Pharmacology, 2017)
Kinin B1 receptor (B1R) contributes to insulin resistance, an early event in type 2 diabetes, through the upregulation and activation of the inducible form of nitric oxide synthase (iNOS), pro-inflammatory cytokines and the oxidative stress. This study addresses the hypothesis that inhibition of kininase 1 (carboxypeptidase M, CPM), the key enzyme involved in the biosynthesis of B1R agonists, could exert the same beneficial effects to B1R antagonism in insulin resistance. Male Sprague-Dawley rats were made insulin resistant with a drinking solution containing 10% D-glucose for a period of 9 weeks. Control rats received tap water. During the last week, kininase 1 was blocked with Mergetpa (1 mg kg-1 twice daily, s.c.) and the impact was determined on insulin resistance (HOMA index), metabolic hormone levels, oxidative stress and the expression of several markers of inflammation by western blot and qRT-PCR. Glucose-fed rats displayed hyperglycemia, hyperinsulinemia, hyperleptinemia, insulin resistance, hypertension, positive body weight gain, and enhanced expression of B1R, CPM, iNOS and IL-1β in renal cortex, aorta and liver. Markers of oxidative stress (superoxide anion and nitrotyrosine expression) were also enhanced in aorta and renal cortex. Mergetpa reversed and normalized most of those alterations, but failed to affect leptin levels and hypertension. Pharmacological blockade of kininase 1 (CPM) exerted similar beneficial effects to a 1-week treatment with a B1R antagonist (SSR240612) or an iNOS inhibitor (1400W). These data reinforce the detrimental role of B1R in insulin resistance and recommend CPM as a new therapeutic target.